Produção de prodigiosina por Serratia marcecens UCP 1549 sob fermentação em estado sólido e avaliação do seu potencial antimicrobiano. - Santos, Renata Andreia dos (2020)
In this work, the potential of Serratia marcescens UCP 1549, gram-negative bacterium isolated from the soil of the semi-arid region of Pernambuco, in the production of prodigiosin under solid state fermentation (FES). Therefore, different agro-industrial substrates (wheat bran, sugarcane bagasse, instant noodle residue, tangerine bark, pineapple peel and pineapple crown), were used in the formulation of the means of production of prodigiosin by FES, obtaining the maximum yield of the red pigment (119.8 g/kg of dry substrate) in the medium consisting of 5 g of wheat bran and humidifiable solution containing sais (KH2PO4, K2HPO4, MgSO4.7H2O and (NH4)2SO4) and 5% post-frying soybean oil. The pigment was identified as prodigiosin by the maximum peak absorbance at 535 nm, Rf of 0.9 in CCD and the functional groups identified by the infrared spectrum (FTIR). Prodigiosin showed stability at different temperature values (0 º C, 10 º C, 50 º C, 70 º C and 100 º C), pH (2, 4, 6, 8, 10, 12 and 14) and concentrations of NaCl (0.1%, 0.2%, 0.5%, 1% and 5%) confirming its potential for application in various industrial, pharmaceutical and medical areas. The raw pigment produced did not show phytotoxic effects in concentrations (0.1%, 0.5% and 1%) for cabbage seeds (Brassica oleracea), lettuce (Lactuca sativa), onion (Allium cepa) and cucumber (Cucumis sativus). Toxicity tests using the microcrustacean Artemia salina, as an aquatic bioindicator, demonstrated low prodigiosin toxicity in concentrations (0.01 mg / L, 0.1 mg / L, 1 mg / L, 10 mg / L and 100 mg / L). The pigment of S. marcescens in antimicrobial action showed a minimum inhibitory concentration (MIC) significant for the bacteria Klebsiella pneumoniae (UCP 1574), Staphylococus aureus (UCP 1576) and Enterococcus faecalis (UCP 1577). Therefore, the results obtained showed the biotechnological potential of S. marcescens UCP 1549 in the production of prodigiosin by FES, using agrifood substrates, which can contribute to reduce production costs, in addition to minimizing the environmental impact.